Berhakkah Anak Berkonflik dengan Hukum Mendapatkan Akses Pendidikan? Studi Deskriptif Sikap Guru terhadap Anak Berkonflik dengan Hukum - Hidayat, Muslim; Husna, Sabiqotul; Thoha, Ahmad Johan Faidlony (UIN Sunan Kalijaga, 2023)
Cases of children in conflict with the law continue to increase in numbers. Teachers' attitudes and views towards children in conflict with the law (ABH) requires empirical study, especially regarding how ABH has the right to continue their education. This study aims to explore teachers' attitudes towards ABH regarding whether they have the right to continue their education. The method used in this research is a quantitative survey with a total of 134 teachers (mean age 36.46). The data collection instrument was a teacher's attitude questionnaire towards children in conflict with the law which was compiled based on cognitive, affective and behavioral aspects (Jain, 2014). The results of the study revealed that teachers' attitudes towards ABH tended to vary, depending on the status of the process being undertaken by students who were involved in criminal cases. The status of ABH who have been sentenced to prison terms is the status that gets the lowest percentage related to the decision and attitude of the teacher considering that ABH has the right to continue school, and gets the highest percentage related to the teacher feeling ashamed when their student is ABH. As for the status of receiving coaching sanctions in social institutions, it is in the context of ABH status that the highest percentage gets from teachers to accept them back and continue their education. Although not all respondents in this study understood the definition of ABH and laws related to ABH, they expressed their attitude of accepting ABH as students with different variations in the context of ABH status itself. The results of this study can provide practical implications in the context of how educational institutions and their instruments can design policies and counseling related to how teachers and other educators respond to children in conflict with the law.